Bimbingan Teknis Penyusunan Laporan Keuangan bagi Pengurus Koperasi di Jawa Barat - Rima Elya Dasuki (LPPM Universitas Koperasi Indonesia, 2023)
Cooperatives as business entities need to provide information on financial conditions that can disclose financial information to all stakeholders, namely by preparing financial reports in accordance with standards that can be accepted by all parties, or the general public. The financial statements of cooperatives reveal the financial conditions of cooperatives, but to measure whetherthe financial condition of cooperatives is good or not, a measurement (analysis) of the financial statements must be carried out. By conducting an analysis of financial reports, cooperatives can take action (action) that is appropriate to anticipate alternative solutions to financial problems that must be carried out by cooperatives in an appropriate manner. Technical guidance on the preparation of financial reports and analysis of financial reports was held by the West Java Province Cooperative Service with 30 participants representing cooperatives in West Java on July 27, 2022. The purpose of this technical guidance activity is to achieve the expected results, namely increasing the competency of cooperative management resources in preparing financial statements